BERITA HOAKS DALAM MEDIA SOSIAL FACEBOOK (PENDEKATAN 5W+1H) - Maryamah, Maryamah; Amalia, Laili (Jurnal Komposisi, 2022)
Hoax news is fake news that is made up or twisted from the real reality. There are many cases or events that did not actually occur but have been made into news and packaged as well as possible so that the public is interested in reading them. Hoax news is now very widespread in various media. Whether it's print media or online media, for example, most people don't care about this. The public can easily believe hoax news and do not hesitate to disseminate it to the public, especially social media Facebook. The type of research used in this study is qualitative research, because the data used in this study are in the form of words and sentences. The description of words and sentences refers to the contents and content of hoax news that spreads on Facebook social media. The data collection techniques in this study included the identification and classification of data, the description of the data, and the interpretation of the data. From the results of the study, it can be concluded that hoax news on Facebook social media, namely creating unrest in the community, destroying social relations, propaganda of religious fanaticism and others. This makes hoax news on Facebook social media even more widespread because of the habit of a person without reading and immediately sharing it without knowing the risks that will occur.